Posterior leaflet augmentation improves leaflet tethering in repair of ischemic mitral regurgitation, - Robb, J. Daniel (Elsevier Science B.V., 2011)
Objectives: Ischemic mitral regurgitation results from annular dilatation, leaflet tethering and leaflet flattening. Undersized annuloplasty corrects annular dilatation but worsens leaflet tethering and flattening. This exacerbation of abnormal leaflet geometry may contribute to poor repair results for ischemic mitral regurgitation (IMR). Using a sheep model of IMR, we hypothesized that posterior leaflet augmentation and less-extreme annular undersizing would relieve tethering and increase leaflet curvature. Methods: Eight weeks after posterolateral infarct, 10 sheep with ≥2+ IMR underwent either a 24-mm planar ring annuloplasty (n = 5) or a 30-mm planar ring annuloplasty with concomitant posterior leaflet augmentation (n = 5). Real-time three-dimensional echocardiography allowed measurement of indices of leaflet curvature and tethering before and after annuloplasty. Results: Comparing pre- and post-repair values in the P1, P2, and P3 leaflet regions, undersized 24-mm ring annuloplasty made no significant difference to mean septolateral curvature (0.23–0.26, 0.33–0.29, and 0.27–0.37 cm(−1), respectively), whereas leaflet augmentation in combination with a 30-mm ring annuloplasty increased septolateral curvature (P1 0.30–1.02, P2 0.31–1.23, and P3 0.35–0.84 cm(−1), p-values ≪ 0.05). The mean tethering angle formed between the annular plane and the posterior leaflet increased in all three posterior regions for the 24-mm ring group (P1 12–23°, P2 26–31°, and P3 16–25°), but decreased in all regions for the group undergoing leaflet augmentation (P1 +5 to −6°, P2 +13 to −13°, P3 +16-15°, all p-values ≪ 0.05). Conclusions: Undersized annuloplasty exacerbates leaflet tethering. Posterior leaflet augmentation with less severe annular reduction increases leaflet curvature and decreases tethering; this technique more completely addresses the pathogenic mechanism of IMR and may improve repair durability.